2014
DOI: 10.28945/2034
|View full text |Cite
|
Sign up to set email alerts
|

Survival Strategies: Doctoral Students’ Perceptions of Challenges and Coping Methods

Abstract: The purpose of this collective case study was to use a critical dialectical pluralistic (CDP) philosophical lens to investigate select doctoral students' perceptions about the challenges that they encountered while in a doctorate program and the coping strategies that they found effective in mitigating these challenges. A major goal of CDP is to empower research participants maximally by giving them the role of participant-researchers. Participants were 10 doctoral students enrolled at a Tier-II university in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 66 publications
2
13
0
2
Order By: Relevance
“…While much research has explored student attrition, factors impacting student persistence in doctoral education has been less well-studied (Rockinson-Szapkiw et al, 2014). As the doctoral experience can be challenging, isolating, and lonely (Dickerson et al, 2014;Lovitts, 2001;Spaulding & Rockinson-Szapkiw, 2012), it is important to understand the resources and skills which facilitate students overcoming these challenges and persevering through their doctoral programs. These include a strong support network, motivation, organization, and time-management skills (McAlpine & Norton, 2006;Spaulding & Rockinson-Szapkiw, 2012).…”
Section: Persistencementioning
confidence: 99%
See 4 more Smart Citations
“…While much research has explored student attrition, factors impacting student persistence in doctoral education has been less well-studied (Rockinson-Szapkiw et al, 2014). As the doctoral experience can be challenging, isolating, and lonely (Dickerson et al, 2014;Lovitts, 2001;Spaulding & Rockinson-Szapkiw, 2012), it is important to understand the resources and skills which facilitate students overcoming these challenges and persevering through their doctoral programs. These include a strong support network, motivation, organization, and time-management skills (McAlpine & Norton, 2006;Spaulding & Rockinson-Szapkiw, 2012).…”
Section: Persistencementioning
confidence: 99%
“…A strong support network facilitates doctoral student persistence (Adorno, Cronley, & Smith, 2015;Dickerson et al, 2014;Martinez, Ordu, Della Sala, & McFarlane, 2013;McAlpine & Norton, 2006;Spaulding & Rockinson-Szapkiw, 2012). Personal supports outside of the academic program, such as partners, spouses, family, and friends, support student persistence (Adorno et al, 2015;Dickerson et al, 2014;Rockinson-Szapkiw et al, 2014). One study found that having a spouse increases the likelihood that students graduate from a doctoral program (Lott, Gardner, & Powers, 2009).…”
Section: Persistencementioning
confidence: 99%
See 3 more Smart Citations